Complaint Mechanism Related to Social Assistance in Gresik District - Rio Aldino Yosevan Silalahi; Wiwik Afifah (Proceeding International Conference on Religion, Science and Education, 2023)
Gluran Ploso village and Wringinanom village are among the villages that have received social assistance from the government. In this writing, the focus is on social assistance in Gluran Ploso and Wringinanom villages. The social assistance in the village has been running for quite a long time, in the course of the social assistance there were findings of problems in the course of the social assistance. The purpose of this study is to find out during the course of social assistance whether there is a very specific problem that is received by the recipients of social assistance in Gresik Regency. The method used in this research is empirical juridical research with a socialological approach. The findings in this study are that the complaint mechanism related to social assistance in Gresik is quite effective, but there is no specific mechanism from the social service, from the sub-district and from the village. After conducting interviews and direct observations in the villages of Gluran Ploso and Wringinanom, it can be concluded that there is still a lack of a complaint mechanism system regarding social assistance except through tksk. So far, the people of Gresik Regency, if they want to make complaints through the command center, but all complaints are still generally online and centered on the information service. communication and also takes a long time. Complaints are important and must be considered for the welfare of recipients of social assistance, where people are currently not satisfied with making complaints because they cannot be carried out optimally and complaints are not resolved properly. Therefore it is necessary to have an application that is centered on social services to make it easier for the public to make complaints.